Evaluating green suppliers from a green environmental perspective. (September 2016) - Tsai, Sang-Bing; Wei, Yu-Min; Chen, Kuan-Yu; Xu, Lei; Du, Peng; Lee, Hung-Chun
A green supply chain requires suppliers to consider products and related environmental management simultaneously and include the principle of environmental protection in management mechanisms. The purpose of the green supply chain is to promote green products and enhance market competitiveness. When industries and companies can establish a set of criteria for assessing green suppliers, the efficiency of resource use can be improved, resource consumption can be reduced, and a green corporate image can be enhanced. On the basis of a green supply chain, this study developed green-supplier evaluation criteria and integrated the decision-making trial and evaluation laboratory method with the analytical network process, forming the decision-making trial and evaluation laboratory-based analytical network process model. The decision-making trial and evaluation laboratory-based analytical network process model was then used to calculate the degree to which the criteria of green suppliers influence one another and the causal relations among the evaluation criteria. Subsequently, the decision-making trial and evaluation laboratory-based analytical network process model was applied to calculate the weights of the criteria and a green-supplier evaluation criteria system was established.